International credit earning in islamic higher education: Mixed-methods evidence from Syekh Abdul Halim Hasan Institute - Agus Purwanto; T. Fadlanil Muflih; Suwardi Lubis (Faculty of Islamic Economics and Business UIN Salatiga, 2025)
This study examines the feasibility and determinants of developing an international credit earning program for the Sharia Economics Study Program at Syekh Abdul Halim Hasan Institute Binjai. Using a sequential explanatory mixed-methods design, the quantitative phase surveyed 200 respondents, revealing strong institutional support and positive attitudes toward internationalization, with mean scores above 4.30 related to improving academic quality and graduate competitiveness. However, financial limitations emerged as the most severe challenge (mean = 4.70), followed by insufficient English proficiency (mean = 2.85) and low curriculum flexibility (mean = 3.20). Qualitative findings from six key informants complement these results, emphasizing institutional readiness, curriculum alignment, and strategic partnerships as core enablers. Informants stressed the need for standardized course mapping, targeted English training, and collaboration with universities that share Islamic economics perspectives. The novelty of this study lies in its integrated model that links attitudinal support, structural readiness, and partnership strategies, offering empirical insights for Islamic higher education internationalization. The study recommends establishing dedicated funding schemes, institutionalizing language support, harmonizing curricula, and implementing pilot collaborations to minimize operational risks. These measures provide practical guidance for building a sustainable and globally competitive credit earning program in Islamic higher education.